2020
DOI: 10.1007/s11357-020-00281-2
|View full text |Cite
|
Sign up to set email alerts
|

I2 imidazoline receptor modulation protects aged SAMP8 mice against cognitive decline by suppressing the calcineurin pathway

Abstract: Brain aging and dementia are current problems that must be solved. The levels of imidazoline 2 receptors (I2-IRs) are increased in the brain in Alzheimer's disease (AD) and other neurodegenerative diseases. We tested the action of the specific and selective I2-IR ligand B06 in a mouse model of accelerated aging and AD, the senescence-accelerated mouse prone 8 (SAMP8) model. Oral administration of B06 for four weeks improved SAMP8 mouse behavior and cognition and reduced AD hallmarks, oxidative stress, and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…Recently, we reported that the amyloidogenic amyloid precursor protein processing pathway was suppressed in senescence‐accelerated mouse prone 8 and 5XFAD mice after treatment with novel I 2 ligands, anticipating the role of I 2 modulation in the amyloid‐β biogenesis (Abás et al, 2020;Griñán‐Ferré et al, 2019; Vasilopoulou, Griñán‐Ferré, et al, 2020). Accordingly, in this study, we demonstrated for the first time that chronic low‐dose treatment with I 2 ligand LSL60101 attenuated the amyloid plaque burden in 5XFAD mice.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Recently, we reported that the amyloidogenic amyloid precursor protein processing pathway was suppressed in senescence‐accelerated mouse prone 8 and 5XFAD mice after treatment with novel I 2 ligands, anticipating the role of I 2 modulation in the amyloid‐β biogenesis (Abás et al, 2020;Griñán‐Ferré et al, 2019; Vasilopoulou, Griñán‐Ferré, et al, 2020). Accordingly, in this study, we demonstrated for the first time that chronic low‐dose treatment with I 2 ligand LSL60101 attenuated the amyloid plaque burden in 5XFAD mice.…”
Section: Discussionmentioning
confidence: 88%
“…Surprisingly, the p‐Tau reduction reached significance in the 5XFAD mice treated with the combination of LSL60101 with donepezil demonstrating, in this case, a putative additive effect of the drugs on tau pathology. Indeed, amelioration of tau pathology has been induced in AD animal models both by donepezil (Yoshiyama et al, 2010) and by I 2 ligand treatments (Griñán‐Ferré et al, 2019; Vasilopoulou, Griñán‐Ferré, et al, 2020). It is possible that the activation of distinct molecular pathways by the two molecules with different modes of actions resulted in a remarkable p‐Tau reduction observed in the donepezil/LSL60101‐treated mice group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 Additionally, phosphorylation of NFATc1 is closely related to the transcription of genes associated with neuroinflammation in AD mice. 24 Notably, the NFATc2 isoform was the most highly expressed in murine microglia cultures, and the ability of the microglia to secrete cytokines was attenuated by deletion of NFATc2 in mouse models of AD. 25 The above findings are strong evidence to support the hypothesis that LRRK2 and NFATc2 selectively modulate pro-inflammatory cytokine expression in extracellular α-synuclein-mediated microglia via TLR2 signaling pathway.…”
mentioning
confidence: 97%
“…Selective 2-BFI [31] decreased OS and altered the levels of antioxidant enzymes in an AD rat model and protected against OSinduced astrocytic cell death. Moreover, our group reported decreased levels of hydrogen peroxide levels and OS markers induced by two new I 2 -IR ligands in aged SAMP8 mice [32].…”
Section: Introductionmentioning
confidence: 81%